Stone Witnesses: armed stelae between the International Tagus and the Douro, Iberian Peninsula - Bueno Ramírez, Primitiva; Barroso Bermejo, Rosa; De Balbín Behrmann, Rodrigo; Salvado, Pedro (SPAL - Revista de Prehistoria y Arqueología, 2019)
Few places in Europe concentrate as many stone steles as the area between the Tagus and the Douro. Archaeology has shown the ample possibilities for mining metal ores, with a clear nerve centre in the modern region of Castelo Branco. From the first discoveries of such unique objects as the Sâo Martinho steles to the current record, the variety and diachronicity of stone steles and menhirs is exceptional on Iberian and European scales. The traditional interpretation that differentiated between the old menhirs and Late Bronze Age steles has been nuanced by the evidence of similar themes and techniques. Another argument presented here is the use of the old stones as the basic material for the production of the Late Bronze Age steles. The human images carved on these memories in stone express elaborate social narratives. The graphic sequences described here demonstrate the political role of these stones and material justification of ancestral pasts. They were undoubtedly imbued with oral tales about old ancestors and new leaders, to justify the order of the economic systems associated with mining and trade in metals.